Entrustable professional activities in nursing education: a scoping review protocol. Issue 10 (3rd October 2022) - Alexander, Nicholas; Maaz, Asja; Peters, Harm; Kottner, Jan
Abstract : Introduction: Entrustable professional activities were introduced in medical education more than 15 years ago. EPAs define units of professional practice that can be fully entrusted to sufficiently competent professionals. Today, EPAs have been developed and implemented in many health professions, as the concept is useful in bridging the gap between competency-based education and the daily tasks health professions have to deal with in the workplace. While some evidence exists in medical education, the role of EPAs in nursing education is not yet fully understood. Therefore, the overall aim of this scoping review is to describe the current body of evidence regarding EPA implementation in nursing education. Methods and analysis: A two-stage screening process will be used during the search phase, in order to screen retrieved abstracts and titles that focus primarily on the discussion of EPA in nursing education in all languages within the last two decades. The electronic databases, OVID (Embase and PubMed combined) and EBSCOhost (CINHAL and ERIC combined), as well as grey literature will be searched. The search period ranges from 1 January 1995 to 31 December 2021. Data will be extracted according to study design, context (geographical location and type of nursing programme), details of EPAs mentioned (title, specifications, limitations and competency domains), as well as evidence of implementation, outcomes and effect sizes. Ethics and dissemination: Ethical approval is not required as this review will be using previously collected data. Review findings will be published in a peer-reviewed journal and presented at scientific conferences.